Risk factors for acute neonatal renal failure - Rambeloson, Setra H.; Samena, Christelle; Rabevazaha, N. A.; Rakotojoelimaria, Elsa H.; Robinson, Annick L. (International Journal of Contemporary Pediatrics, 2022)
Background: Acute neonatal renal failure is a health problem. Its risk factors and its clinical and evolutionary profile remain unknown in the Malagasy context. The main objective of this study was to determine its risk factors. Methods: This was a 14 month, single-center, retrospective, case-control study (November 2018 to December 2019). The cases were represented by newborns hospitalized and presenting an hypercreatininaemia (value >133 µmol/l or according to the KDIGO criteria) and controls by neonates without an hypercreatininaemia. One case was matched to 2 controls. Results: We included 75 cases. The prevalence was 14.5%. The mean age was 5±6.78 days (p=0.006). The sex ratio was 1.27. The mean gestational age was 36.69±3.84 WA (p=0.66). The mean serum creatinine value was 180.32 µmol/l. Thirty-one newborns had died (41.3%). The risk factors were: sepsis (OR=9.37, p≤0.001, CI=3.03, 33.5), perinatal asphyxia SARNAT 2 (OR=4.52, p=0.007, CI=1.53, 13.8) and SARNAT 3 (OR=7.90, p=0.021, CI=1.56, 60.4), increased weight loss (OR=4.04, p=0.006, CI=1.51, 11.2) and respiratory distress (OR=2.76, p=0.005, CI=1.37, 5.77). Conclusions: The risk factors were consistent with the data in the literature. Better management of parturients and the newborn as well as monitoring of serum creatinine in hospitalised newborns are recommended.